Effect of gamma irradiation and salt on the physical properties and microbiological quality of turmeric paste (Curcuma longa) - Wan Ibadullah, Wan Zunairah; Brishti, Fatema Hossain; Mahmud Ab Rashid, Nor-Khaizura; Mohammad Rashedi, Ismail-Fitry; Zainal Abedin, Nur Hanani; Shukri, Radhiah; Mohd Dzomir, Ahmad Zainuri (Hibiscus Publisher Enterprise, 2024)
Turmeric paste is prized for its color, aroma, and antioxidant properties, serving as a key ingredient in both culinary and traditional medicinal practices. The surge in spice consumption reflects growing consumer awareness of healthy lifestyles and the need for natural preservatives in processed foods. However, the paste's high water content poses challenges for storage stability, necessitating safe preservation methods without chemical additives. Salt addition, a traditional preservative, raises concerns about excessive sodium intake. Spice irradiation emerges as a recognized preservation technique, reducing losses, enhancing shelf life, and ensuring microbiological safety. This study aims to evaluate the storage stability of turmeric paste treated with irradiation (4, 6, and 8 kGy) and salt (10, 20, and 30%) under varying temperatures (4-6°C and 25-27°C) over 30 days. Results indicate minimal differences in water content, pH, color, and curcumin levels between irradiated and salt-treated paste. Salt-treated paste exhibits superior microbiological quality, suggesting it provides better storage stability compared to irradiation. However, considering health concerns related to high salt intake, a formulation combining 20% salt with 8 kGy irradiation stored at chiller temperature is recommended for optimal storage quality.